Tuberculin Test on Infants and Children Who Had Been Given BCG Vaccination During Neonatal Period - Fauzah Fauzah; Riza I. Nasution; Ansarudin Nasution; Ridwan M. Daulay; Helmi M. Lubis; Zakaria Siregar (Indonesian Pediatric Society, 1996)
On one hundred and seven children 3 months to 5 years old who had received BCG vaccination during neonatal period were reviewed with tuberculin test. This study were conducted at the children's and maternity Hospital Sri Ratu Medan for 4 months. They comprised 61 males and 46 females with moderate to well nouÂrished. Tuberculin test was seen at 72 hours after the injection. Tuberculin test was said positive if the induration was >5 mm was found. Positive tuberculin test were found on 58 children (54.2%), out of which 49 children (84.5%) were <1 year old and 9 children (15.5%) were 1 year old. Significant difference was found in positive tuberÂculin test between child group of <1 year old compared to those of >1 year old (p <0.001). Diameter of induration was between 0-10 mm. Most of the children (51 = 47.7%) were having diameter of 5-9 mm. Median diameter of induration of tuberculin test was significant difference between child group of <1 year with those of >1-2 years, >2-3 years, >3-4 years and >4-5 years old respectively (p<0.01). BCG scar did not show significant relationship with tuberculin test result and age.